Potensi Bacillus cereus dalam produksi biosurfaktan - Setiani, Nur Asni; Agustina, Nia; Mardiah, Irma; Hamdani, Syarif; Astriany, Dewi (Jurnal Biologi Udayana, 2020)
Biosurfactants from microorganisms have stable physical and chemical properties, environment friendly, biodegradable, renewable, cheaper and low toxicity that can be used in the pharmaceutical industry as antibacterial. The aim of this study was to examine the emulsification and characterization of biosurfactant from Bacillus cereus . Hemolysis and spreading oil tests was performed as an initial screening. Biosurfactant production was carried out by growing bacteria on oil-enriched media with shaker system for 7 days. The supernatant was measured for biosurfactant activity through an emulsification index and characterized using thin layer chromatography and antibacterial qualitative testing. The emulsification index on days 0, 1, 3, 5, and 7 showed percentage in sequence 44,83%, 48,28%, 51,72%, 46,43%, and 51,50%. The formation of red stains on TLC plates with ninhydrin appearance showed lipopeptide groups. Antibacterial testing using Escherichia coli and Staphylococcus aureus showed the formation of clear zones around the disk paper. Bacillus cereus can produce biosurfactants of the lipopeptide group with the largest emulsification index of 51.72% and has antibacterial activity against both gram positive and gram negative.